2012
DOI: 10.1139/g2012-013
|View full text |Cite
|
Sign up to set email alerts
|

Identification and phenotypic description of new wheat – six-rowed winter barley disomic additions

Abstract: To increase the allelic variation in wheat-barley introgressions, new wheat-barley disomic addition lines were developed containing the 2H, 3H, 4H, 6H, and 7H chromosomes of the six-rowed Ukrainian winter barley 'Manas'. This cultivar is agronomically much better adapted to Central European environmental conditions than the two-rowed spring barley 'Betzes' previously used. A single 'Asakaze' × 'Manas' wheat × barley hybrid plant was multiplied in vitro and one backcross plant was obtained after pollinating 354… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Asakaze and barley cv. Manas cultivars in order to increase the allelic variation of wheat (Molnár-Láng et al 2012). It has recently been reported by Darkó et al (2015), that among the added barley chromosomes tested (2H, 3H, 4H, 6H, 7H), the 7H addition line has elevated salt tolerance as compared to the wheat parent, and that the salt tolerance of the 7H addition line is associated with elevated osmotic adjustment capacity, similar to that found in Manas.…”
Section: Introductionsupporting
confidence: 58%
“…Asakaze and barley cv. Manas cultivars in order to increase the allelic variation of wheat (Molnár-Láng et al 2012). It has recently been reported by Darkó et al (2015), that among the added barley chromosomes tested (2H, 3H, 4H, 6H, 7H), the 7H addition line has elevated salt tolerance as compared to the wheat parent, and that the salt tolerance of the 7H addition line is associated with elevated osmotic adjustment capacity, similar to that found in Manas.…”
Section: Introductionsupporting
confidence: 58%
“…Asakaze and barley cv. Manas (Molnár-Láng et al 2012) in order to increase the allelic variation in the introgression lines. In this way, a set of disomic addition lines (2H, 3H, 4H, 6H and 7H) and several ditelosomic lines (3HS and 7HL) of Asakaze-Manas were produced (Molnár-Láng et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Manas (Molnár-Láng et al 2012) in order to increase the allelic variation in the introgression lines. In this way, a set of disomic addition lines (2H, 3H, 4H, 6H and 7H) and several ditelosomic lines (3HS and 7HL) of Asakaze-Manas were produced (Molnár-Láng et al 2012). Their saltstress responses have not yet been characterized, but an earlier preliminary study showed that increasing salt concentrations caused a less pronounced decline in net photosynthesis in the Asakaze-Manas 7H addition line than in the parental variety Asakaze, suggesting that this line might be a good candidate for improving the salt tolerance of wheat (Dulai et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat-barley disomic addition lines (2H, 3H, 4H, 6HS, 7H, 1HS isochromosome) were produced and identified using molecular cytogenetic methods from hybrids between winter wheat line Mv9kr1 and the German two-rowed winter barley Igri Molnár-Láng 2007, 2010). In order to increase the allelic variation in wheat/barley introgressions, new wheat/barley disomic addition lines were developed containing the 2H, 3H, 4H, 6H and 7H chromosomes of the six-rowed Ukrainian winter barley cultivar Manas (Molnár-Láng et al 2012). This cultivar is agronomically much better adapted to Central European environmental conditions than the two-rowed spring barley cultivar Betzes previously used.…”
Section: Introductionmentioning
confidence: 99%
“…The wheat-barley addition lines produced in various cultivar combinations (CS 9 Betzes, Mv9 kr1 9 Igri, Asakaze 9 Manas) had several morphological traits in common (Molnár-Láng et al 2012). The 4H additions had the best fertility and 7H the lowest in all three combinations.…”
Section: Characterization and Exploitation Of Wheat-barley Introgressmentioning
confidence: 99%